Resistance of the national collection of rice varieties to phytophagous pests - Dudchenko, T.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of the field evaluation of the national collection of rice varieties, for resistance to Cricotopus silvestris Fabr., Hydrelia grisseola Fall., Ephydra macellaria Egg. & Schizaphis graminum Rond. by using an improved method of determining all types (antixenosis, antibiosis, evasion and tolerance) and adaptive resistance, are provided. Under conditions of 2011, among the 23 examined samples 3 varieties turned out to be resistant (with a score of 6) to Cricotopus silvestris Fabr., 1 to Hydrelia grisseola Fall., 2 to Ephydra macellaria Egg. In 2012, complex resistance (among 41 rice varieties) was observed in: UIR 3482, Flagman, Snezhynka, KOP-383-93 (red), which can be harnessed in a program of breeding resistant varieties. Rice samples exhibited different sensitivity to the scheme: mixed herbicide penoksulam + tsyhalofop-butyl and insecticide lambda tsyhalotryn after 10 days.